Node‐positive hypopharyngeal cancer treated by (chemo)radiotherapy: Impact of up‐front neck dissection on outcome, toxicity, and quality of life. Issue 9 (21st August 2012) - Al‐Mamgani, Abrahim; Meeuwis, Cees A.; van Rooij, Peter H.; Mehilal, Robert; Basdew, Harie; Sewnaik, Aniel; Levendag, Peter C.
Abstract Background To investigate the impact of up‐front neck dissection on the outcome of patients with node‐positive hypopharyngeal cancer (HPC) treated with (chemo)radiation. Methods Of 135 consecutive patients with node‐positive HPC, 32 patients underwent up‐front neck dissection followed by (chemo)radiation (group 1), and 103 patients received definitive (chemo)radiation (group 2). Results The 3‐year regional, local and distant control for groups 1 and 2 were 92% versus 87% (p = .37), 84% versus 72% (p = .15), and 80% versus 62% (p = .08), respectively. High T classification was the only significant predictor for poor overall survival on multivariate analysis (OR = 3.0, p = .02). Acute and late toxicities and the prospectively assessed quality of life were comparable in both groups. Conclusion Upfront neck dissection followed by (chemo)radiation did not negatively impact on oncologic outcomes, toxicity, or quality of life and therefore is to be regarded as a safe and effective treatment option for small HPC with bulky nodal disease, especially in busy radiation departments with unacceptably long waiting time for definitive (chemo)radiation. © 2012 Wiley Periodicals, Inc. Head Neck, 2013